A study of association between dental health status and pregnancy - Gupta, Bhavana; Siddique, Attiuddin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: To study the association between dental health status and pregnancyin rural India. Methods: The cohort study was carried out in the department of Obstetrics and Gynecology at Integral Institute of Medical Sciences and Research, Lucknow from March 2012 to April 2013, for the period of 1year. The dental health statuses of 600 antenatal cases were studied. The prevalence of gingivitis, dental caries and periodontal disease were studied. The association between poor oral hygiene, gingivitis and dental caries were studied in the pregnant women. Results: In the study the prevalence of dental caries, gingivitis and periodontal disease were 90%, 98% and 90.33% respectively. The antenatal cases with poor oral hygiene were 2.5 times more likely to have dental caries. OR 0.0138, 95%CI (0.0033 to 0.0570) Z statistic 5.908, P<0.0001.The antenatal cases with poor oral hygiene were 20times more likely to have gingivitis (OR 0.0045, 95% CI (0.0006-0.0365) Z statistic 5.077, P<0.0001).